Essential amino acid carbon isotope ratios as indicators of marine macrophyte response to environmental variation - Yun, Hee Young; Kim, Sangil; Choi, Hyuntae; Kim, Ji-Eun; Park, Sang Rul; Shin, Kyung-Hoon (Frontiers in Marine Science, 2024)
The carbon isotope ratios (δ 13 C) of essential amino acids (EAAs), including valine, leucine, isoleucine, threonine, and phenylalanine, in producers are crucial for explaining food-web structures in marine ecosystems. However, few studies have tested the variability of δ 13 C-EAA values in marine macrophytes, such as seagrass and macroalgae, under changing environmental conditions. In this study, we examined the responses of δ 13 C-EAA values in macrophytes to environmental changes and explored their usefulness in characterizing macrophyte groups and local environments. We tested seagrass and macroalgae collected at different spatial and temporal scales in the field, as well as lab-cultured Ulva algae at various temperature gradients (12℃, 20℃, and 27.5℃) with additional nitrogen sources. The results revealed that δ 13 C-EAA values in macroalgae were significantly altered by seasonality and the interactive effects of temperature and nitrogen addition in comparison with meancentered δ 13 C-EAA values (normalized δ 13 C-EAA values relative to the mean of the overall EAAs). The δ 13 C-EAA values detected in macroalgae within a local environment correlated with those of a co-occurring grazer, Caprella. Based on mean-centered δ 13 C-EAA values, macrophyte groups were distinguishable from other group (i.e., the bacteria group) even under diverse environmental conditions. Moreover, the seagrass group did not overlap with the green and the brown macroalgal group, but overlapped considerably with the red macroalgal group. These results suggest that the macrophyte-specific mean-centered δ 13 C-EAA values may be fairly consistent across broad spatial and temporal scales. Despite significant variation in δ 13 C-EAA values, the consistency in mean-centered δ 13 C-EAA values among specific macrophyte groups provides valuable insight into the characteristics of local trophic bases in regions under pressure from dramatic environmental changes.